Mixed genotypes of Orientia tsutsugamushi in conserved genes and a single immune-dominant tsa56 genotype discovered from a patient with scrub typhus in Hainan Island, China: a case report - Chuanning Tang; Liyuan Zhang; Yi Huang; Wenhui Mai; Liying Xue; Gaoyu Wang; Shu Wen; Ruoyan Peng; Kunliang Wu; Xiuying Tian; Hua Pei; Jiang Du; et al. (BMC Infectious Diseases, 2022)
Abstract Background Orientia tsutsugamushi (O. tsutsugamushi), an obligate intracellular bacterium, is transmitted to humans through infected larval trombiculid mite bites, causing scrub typhus. Mixed genotypes of O. tsutsugamushi in canonical conserved genes were reported in 8–25% of blood samples from patients. Yet, there are few clinical descriptions of these mixed O. tsutsugamushi-infected patients. Case presentation We report a patient with scrub typhus complicated with pulmonary involvement and hepatic dysfunction, who carried mixed genotypes of the conserved genes but had a single immune-dominant 56-kDa type-specific antigen (tsa56) genotype. The patient was successfully recovered by doxycycline treatment. Conclusions In this reported case, both patient’s eschar and blood samples have repeatedly shown the same results, i.e., no variants were discovered in tsa56 gene that bears multiple hypervariable regions. Whereas the selected highly conserved genes were identified with up to 32 variants in a 2700 base-pair concatenated sequence. The prevalence, disease severity and mechanism of these single-tsa56-genotype mixed infections remain to be investigated on a large scale with more cases.